An MRI, SPECT and Neuropsychological Study of a Patient Presenting with Capgras Syndrome - J. Mackie; K. P. Ebmeier; R. E. O'Carroll (Behavioural Neurology, 1994)
A 25 year old male patient presented with the “delusion of doubles” (Capgras syndrome). The patient underwent detailed neuropsychological, single photon emission computed tomography (SPECT) and magnetic resonance imaging (MRI) investigations. The neuropsychological results indicated that he was of average premorbid intelligence, which was consistent with current estimates, and had a degree of everyday memory dysfunction which was below norms derived from healthy controls, but was average relative to schizophrenic norms. He demonstrated average or above average recognition memory for patterns, spaces or words, but exhibited a marked and disproportionate impairment in face recognition, performing at the 5th percentile. In addition he demonstrated markedly impaired performance on various tests of executive function. MRI scanning revealed no focal abnormality; slight ventricular dilatation was noted. SPECT scanning, however, revealed marked right/left asymmetries of tracer uptake, restricted to occipital and calcarine cortices. These asymmetries were well outside those derived from a cohort of healthy controls. These results are discussed in relation to current neuropsychological models of Capgras syndrome.